Organizational Ecology and Industrial Economics: a Comment on Geroski - Barron, D (2001)
Geroski's discussion of organizational ecology from the point of view of an industrial economist is useful and illuminating. However, I believe that there are a few areas in which someone not familiar with the ecological literature might be misled. I therefore provide a slightly more detailed discussion of work done by ecologists in three key areas: the relationship between density, legitimacy, competition and the rates at which organizations enter and exit a population; the ways in which ecologists conceptualize and model legitimacy; and the theory of structural inertia.